Faktor-Faktor yang Mempengaruhi Keberhasilan Usaha Mustahik pada Program Zakat Produktif di Baznas Kabupaten Tasikmalaya - Rahmawati, Agnia; Zulfikri Rahmat, Biki; Friantoro, Dian (UPT Penerbitan Universitas Jember, 2025)
This study aims to analyze the factors influencing the business success of mustahik in the productive zakat program managed by BAZNAS Tasikmalaya Regency. Using a quantitative approach and purposive sampling, this research involved 71 mustahik beneficiaries of capital assistance from the BMM (BAZNAS Microfinance Masjid), Z Chicken, and Z-Mart programs. The variables examined include business assistance, business capital, business motivation, and business environment, with multiple regression analysis as the main analytical tool. The findings indicate that all variables have a positive and significant effect, both partially and simultaneously, on business success. These results highlight the importance of assistance, capital, motivation, and the business environment in fostering the economic independence of mustahik. Beyond its practical implications for BAZNAS in strengthening economic empowerment strategies, this research also contributes to the theoretical development of Islamic philanthropy studies, particularly in positioning productive zakat as a sustainable instrument for poverty alleviation.